Redesign Automatic Flashlight Identification Signal 1.0 (AFIS1.0) on KRI with Kansei Engineering and Ethnography Methods - Susyanto, Agung; Sudiarno, Adithya; B, R. Bambang Ispri (Jurnal Perikanan dan Kelautan, 2024)
AFIS 1.0 is a helpful communication tool for sending and receiving automatically operated Morse lamp signal news. In this study, researchers developed AFIS 1.0 because there were still some shortcomings in the previous device, namely that AFIS 1.0 was still operated using a PC, could not store its power, could not be portable, and was not equipped with recorded data. This study aims to identify the attributes of AFIS 1.0, redesign the prototype AFIS 1.0 according to the attributes obtained and test the results of the prototype AFIS 2.0. The method used in this study is ethnography, where the researcher directly observes respondents in the field. Kansei engineering is used to translate respondents' psychological feelings and needs into product design parameters. The results of this study are in the form of a prototype AFIS 2.0 with the Android operating system, equipped with a rechargeable battery, can be installed permanently and portable, equipped with data recording, Morse complex and the tool can be operated automatically or manually. In testing the results of the prototype AFIS 2.0 conducted by the Head of KRI SIM-366 and the Head of KRI Nala-363, it was stated that the tool can be appropriately operated so that AFIS 2.0 can answer respondents' wishes in the field. With the development of AFIS 2.0, it is hoped that communication with soldiers on KRI will be more straightforward in sending and receiving news of Morse lamp signals.